High Performance Supercapacitor Using Catalysis Free Porous Carbon Nanoparticles - Ali, Gomaa A. M.; Shoriya Aruni, Abdul Manaf; Kumar, Anuj; K. F., Chong; Hegde, Gurumurthy (IOP Publishing, 2014)
Very high supercapacitance values are obtained using catalyst free porous carbon nanoparticles (PCNs). The obtained PCNs have a porous structure with fine particles 35 nm in size. The specific capacitance of PCNs is 343 F g− 1 and 309 F g− 1 at 5 mV s− 1 and 0.06 A g− 1, respectively. PCNs shows a high cyclic stability of about 90% and high columbic efficiency of 95% over 2500 cycles at 1 A g− 1. Impedance spectra show low resistance of PCNs, supporting their suitability for supercapacitor electrode application.